Penerapan Terapi Isometric Handgrip Exercise terhadap Gangguan Mobilitas Fisik Pasien Stroke - Meisy Ananda Saputri; Renny Triwijayanti (Ners Akademika, 2025)
Purpose: This study aims to analyze the effectiveness of Isometric Handgrip Exercise therapy in improving physical mobility among stroke patients who experience muscle weakness and motor impairment. The research was motivated by the increasing incidence of non-hemorrhagic stroke cases recorded at Siti Fatimah Az-Zahra Regional Hospital in South Sumatra Province. Method: This research employed a descriptive method. Data were collected through structured interviews, direct observations, and physical examinations. Muscle strength was measured using a handgrip dynamometer before and after the application of Isometric Handgrip Exercise therapy to evaluate changes in mobility and strength. Result: The findings indicated a significant improvement in the patients’ physical mobility after the implementation of Isometric Handgrip Exercise therapy. Both observed patients showed increased muscle strength and better control of extremity movement, suggesting the therapy’s positive impact on functional recovery. Conclusions: Isometric Handgrip Exercise therapy is effective in addressing impaired physical mobility in stroke patients. The intervention enhances muscle performance and contributes to restoring motor function in affected limbs. Limitation: The study involved only two participants and used a descriptive design, which limits the generalizability of the findings. Future research with larger samples and experimental methods is required to validate the results. Contribution: This study contributes to the development of rehabilitation nursing practices by providing evidence that simple, low-cost, and non-invasive exercises such as Isometric Handgrip therapy can effectively support stroke recovery and improve patients’ quality of life.